2021
DOI: 10.1108/afr-07-2020-0105
|View full text |Cite
|
Sign up to set email alerts
|

A Cambodian smallholder farmer's choice between microfinance institutes and informal commercial moneylenders: the role of risk attitude

Abstract: PurposeThe purpose of this paper is to examine the extent to which individual risk attitude determines a Cambodian smallholder's choice between a commercial informal loan and a credit from a licensed microfinance institution.Design/methodology/approachThe paper analyzes a sample of smallholder farmers in the Ratanakiri province in northeastern Cambodia, a country with a long history of microfinance and a saturated microcredit market. Employing a binary and a multinomial logit model, this paper assesses the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…Research found that people are more attracted to loan sharks due to their flexibility in providing the services and has even reduced the demand for institutional credit (Ray, 2019). Taking loans from loan sharks was driven by community knowledge of the low risk they will receive (Possner et al, 2022) or failure to access banking (Scaglione, 2014). Loan sharks continue to have their existence in society (Venittelli, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research found that people are more attracted to loan sharks due to their flexibility in providing the services and has even reduced the demand for institutional credit (Ray, 2019). Taking loans from loan sharks was driven by community knowledge of the low risk they will receive (Possner et al, 2022) or failure to access banking (Scaglione, 2014). Loan sharks continue to have their existence in society (Venittelli, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Small farmers in Cambodia are more likely to use the services offered even though the interest rates were high if they are unaware of the dangers of borrowing from loan sharks (Possner et al, 2022). Another study conducted by Ray revealed that in rural Indian communities, the flexibility provided by loan sharks services had appeared as an attractive point that made the services more preferred by the community (Ray, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, farmers seeking credit are likely to turn to the informal sectors offering low-collateral loans at high interest rates; as pointed out by Binswanger and Silas (1983), risk-averse individuals prefer high interest over collateral requirements to avoid high additional costs at the default stage. Possner et al (2021) analyzed Cambodian smallholders' credit demand and found that less risk-averse individuals tend to take up riskier and generally more expensive informal loans. Beyond risk attitude, actual or perceived risk can also influence the demand for credit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Problematika rentenir tidak hanya terjadi di Kota Langsa, bahkan di berbagai negara juga mengalami kasus yang sama terkait dengan permasalahan rentenir, seperti penelitian Annkathrin Possner, Selina Bruns dan Oliver Musshoff yang dilakukan di negara Kamboja (Possner et al, 2021) mengambarkan bahwa para petani kecil memilih rentenir sebagai kreditur karena sedikit resiko. Penelitian Bruce R. Bolnick di Malawi (Bolnick, 1992), Claudia N. Berg, M. Shahe Emran dan Forhad Shilpi di Banglades (Berg et al, 2013) dan penelitian Louise Signal, Tolotea Lanumata, Sharron Bowers di New Zealand (Signal et al, 2012a).…”
Section: Pendahuluanunclassified